2011
DOI: 10.1111/j.1346-8138.2011.01459.x
|View full text |Cite
|
Sign up to set email alerts
|

Dramatic impact of a Psoriasis Area and Severity Index 90 response on the quality of life in patients with psoriasis: An analysis of Japanese clinical trials of infliximab

Abstract: European S3 Guidelines on the systemic treatment of psoriasis in 2009 propose 75% or more improvement in the Psoriasis Area and Severity Index from baseline (PASI 75) and a Dermatology Life Quality Index (DLQI) of 0 or 1 as treatment goals. However, the relationship of these two parameters is yet to be clarified. Herein, we analyzed the data pooled from two Japanese phase III clinical trials on psoriasis with infliximab to clarify the PASI response necessary to achieve a DLQI of 0 or 1. Of the 90 patients, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
64
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 21 publications
(43 reference statements)
4
64
0
Order By: Relevance
“…A positive relationship between TSI and clinical efficacy (PASI75 or PASI90) assessed at the same time was reported in 4 studies (89 patients) (28,30,32,34). Long-term responders (over 18 months) had detectable TSI (32).…”
Section: Relationship Between Trough Serum Infliximab Levels (Tsi) Anmentioning
confidence: 60%
See 1 more Smart Citation
“…A positive relationship between TSI and clinical efficacy (PASI75 or PASI90) assessed at the same time was reported in 4 studies (89 patients) (28,30,32,34). Long-term responders (over 18 months) had detectable TSI (32).…”
Section: Relationship Between Trough Serum Infliximab Levels (Tsi) Anmentioning
confidence: 60%
“…Eight were original articles (4 randomised clinical trials (3,(26)(27)(28), 3 prospective open studies (29)(30)(31) and one observational study (32)). Two additional articles (33,34) were duplicate publications of selected studies, but were retained in the analysis because they provided additional data on assessment of serum IFX concentrations. Population characteristics, infliximab regimen, methods and times of serum IFX concentration assays are summarised in Table I and Table SI 1 .…”
Section: Literature Search and Characteristics Of Articles Included Imentioning
confidence: 99%
“…Although the complete clearance of skin lesions may be regarded as the ultimate treatment goal for psoriasis, a PASI 75 response has been proposed as a practical and realistic treatment goal [40]. Meanwhile, Torii et al [42] in their study on infliximab considered that a PASI 90 response is necessary to achieve a treatment goal stated in the European S3 guidelines: a DLQI of 0 or 1 (no effect on patient’s QoL). More recently Elewski et al [43] in a study on secukinumab have shown that psoriatic patients with a PASI 90 response achieve greater health-related QoL improvements than those with a PASI 75–89 response and concluded that PASI 90–100 is a relevant therapeutic goal in moderate-to- severe psoriasis.…”
Section: Hrqol Assessment In Dermatological Guidelinesmentioning
confidence: 99%
“…1,2 Advances in understanding the pathogenic cytokine network of psoriasis have led to the development of new treatments [3][4][5] that provide greater efficacy in terms of complete skin clearance. [6][7][8][9] The motivation to completely clear psoriasis plaques from the skin of patients has grown in response to accumulating evidence that residual skin disease can affect a patient's health-related quality of life [10][11][12] similar to that associated with chronic conditions such as type 2 diabetes. 13 Ixekizumab, a recombinant, high-affinity, humanized, IgG4-κ monoclonal antibody, selectively binds and neutralizes interleukin 17A (IL-17A), the proinflammatory and primary effector cytokine of type 17 helper T (Th17) cells.…”
mentioning
confidence: 99%